DIFFERENTIAL ASSOCIATION OF HORMONE THERAPY WITH CHANGE IN GLOBAL COGNITION AND INCIDENT DEMENTIA BY HEARING STATUS. (11th November 2018) - Armstrong, N; Espeland, M; Masaki, K; Deal, J; Lin, F; Resnick, S; Rapp, S
Abstract: Hearing loss and hormone therapy are independently associated with dementia, yet joint effects of hearing loss and hormone therapy could be associated with greater decline in global cognition and increased risk of dementia. Using data on self-reported hearing loss (moderate/severe vs. mild/normal hearing) and hormone therapy (0.625 mg of conjugated equine estrogens [CEE], 0.625 mg of conjugated equine estrogens plus 2.5 mg of medroxyprogesterone acetate [CEE+MPA], and respective placebos) from 7, 220 post-menopausal women enrolled in the Women's Health Initiative Memory Study, we modeled multivariable linear mixed effects models with change in global cognition, as defined by Modified Mini Mental State Examination, as an outcome and accelerated failure time models with adjudicated dementia diagnosis as an outcome. Models were adjusted by demographic characteristics, co-morbidities, and depressive symptoms. After adjustment, post-menopausal women with hearing loss and CEE had lower global cognition (β=-0.841, 95% CI: -1.647, -0.035) and less steep decline in global cognition (β=0.104, 95% Confidence Interval, [CI]: 0.010, 0.199), as compared to those with normal hearing and placebo. After adjustment, post-menopausal women on CEE+MPA with (Time Ratio, [TR]=0.68, 95% CI: 0.52, 0.90) and without (TR=0.60, 95% CI: 0.37, 0.96) hearing loss have faster time to dementia than those with normal hearing and placebo. Hormone therapy seems to be a more potent driver of cognitive outcome regardless of hearing status.